Diagnostic value of ultrasound in children with transverse testicular ectopia - Zhou, Wei; Li, Shoulin; Wang, Hao; Yin, Jianchun; Liu, Xiaodong; Jiang, Junhai; Zhou, Guanglun; Wen, Jianguo (Frontiers in Pediatrics, 2022)
【Abstract】 Objective To investigate the diagnostic value of ultrasound in children's Transverse Testicular Ectopia (TTE). Methods We retrospectively study all TTE cases diagnosed in our hospital from January 2017 to December 2021. All cases were evaluated by ultrasound examination, and compared to physical examination and Diagnostic Laparoscopy results. Results This study included 14 TTE in total, the median age was 1.08 years.In the 14 TTE, physical Examination found 10 TTE, of which 9 testes were located in the opposite scrotum, and 1 testical were located on the opposite groin, and the other 4 testes were not touched by physical examination.All cases were diagnosed with preoperative ultrasound, and 9 testes were located in the opposite scrotum, and 2 testes were located were located on the opposite groin, and 3 testes were located next to the opposite iliac vessel in abdominal cavity.Preoperative ultrasound showed ectopic spermatic cord in 6 cases (6/14, 42.8%) and persistent mullarian duct syndrome (PMDS) in 1 case (1/14, 7%).Diagnostic laparoscopy finally confirmed 14 cases of TTE, which was consistent with preoperative ultrasound, and the coincidence rate was 100% (14/14).Among the 14 cases of TTE, diagnostic laparoscopy showed that 12 cases had ectopic spermatic vessels and vas deferens (12/14, 85.7%), and 6 cases associated with PMDS (6/14, 42.8%).When TTE associated with ectopic spermatic cord and PMDS, the diagnostic performance of diagnostic laparoscopy was better than preoperative ultrasound (P<0.05). The testis volume of the affected side of TTE was smaller than the contralateral testis (P<0.05).Conclusion Ultrasonography is very helpful for the preoperative diagnosis of TTE in children, and it is suitable as a non-surgical method for locating ectopic testis.Preoperative assessment of the exact presence of PMDS is difficult and unclear. This may be related to factors such as pelvic developmental stages in infancy, examination techniques and atypical imaging findings of PMDS.